A STUDY ON ARTIFICIAL INTELLIGENCE IN EDUCATION (International journal of artificial intelligence, 2024)
The integration of artificial intelligence technology into the education system is of great importance in improving educational processes and developing an individual approach. This article analyzes the contribution of artificial intelligence to education, its possibilities for automating the educational process, creating programs adapted to students, and increasing inclusiveness in education. It also highlights the effective use of artificial intelligence tools and the problems arising from them. It is noted that this technology is a necessary factor for improving the quality of education and its further development in the future.